The Psalms in French and Ukrainian Literatures: Versions by Clément Marot and Taras Shevchenko - Bigun, O. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The article deals with the first exemplars of the psalms translations into French and Ukrainian. Sociohistorical factors leading to a departure from canonical languages are analyzed. Similarities and differences in the process of psalms translation into national languages are identified. Translations of psalms are spread in those countries where the national language and literature are at the stage of search and formation. At that, both in Protestant and Catholic poetry one can easily trace the tendency for the departure from the original, the manifestation of individual author’s origin due to the movements for the Reformation and the Counter-Reformation which considerably changed attitude towards individuality. The Book of Psalms, having its problematic and thematic elaboration of the expression of human feelings, distinctive lyricism, strength and intensity of emotions, bright ideas, providential vigour, precision and great simplicity in the poetic representation of religious feeling, in this case became a universal model prototext which inspired poets to its further actualization